Prefabricated Systems: Principles of Construction - Knaack, Ulrich; Chung-Klatte, Sharon; Hasselbach, Reinhard (Birkhäuser, 2012)
For a number of years, modular construction – the use of prefabricated elements in architecture – has once again become a subject of lively discussion and debate. Long written off as monotonous, today’s building components are actually highly differentiated and capable of supporting and enhancing the architect’s creativity. Numerous structures work with prefabricated components; for single-family homes the figure is ninety-eight percent, and modular systems are available that meet high aesthetic standards.This book provides an overview of the various different systems and their possible uses, particularly in the areas of housing, office, and industrial buildings. It explains the processes and components of modular construction and the behavior of the various materials when this construction approach is used. The authors offer strategies for planning and designing with prefabricated systems so that the architect can use them productively.Numerous drawings explain the principles of modular construction, while built examples forge a link between those principles and the practical activity of building. Seit einigen Jahren wird der Systembau, die Verwendung von vorgefertigten Elementen in der Architektur wieder engagiert diskutiert. Lange als monoton abgestempelt, weisen heutige Bauelemente in Wirklichkeit einen hohen Differenzierungsgrad auf, der die Kreativität der Architekten nachhaltig stützen und verstärken kann. Zahlreiche Bauten arbeiten mit solchen vorgefertigten Elementen – im Bereich Einfamilienhäuser trifft dies heute auf 98 Prozent zu und es sind ästhetisch anspruchsvolle Modulsysteme erhältlich. Dieses Buch stellt übersichtlich die verschiedenen Systeme und ihre Einsatzmöglichkeiten insbesondere im Wohnungs-, Büro- und Industriebau vor. Die Prozesse und Komponenten im Systembau werden erklärt, und das Verhalten der unterschiedlichen Materialien bei dieser Bauweise erläutert. Die Autoren stellen Strategien für Planung und Entwurf mit präfabrizierten Systemen vor, damit diese vom Architekten nutzbringend eingesetzt werden können. Zahlreiche Zeichnungen erklären die Prinzipien im Systembau, gebaute Beispiele sorgen für den Brückenschlag zur Baupraxis.